Characterizing structural neural networks in de novo Parkinson disease patients using diffusion tensor imaging. Issue 12 (28th July 2016) - Nigro, S.; Riccelli, R.; Passamonti, L.; Arabia, G.; Morelli, M.; Nisticò, R.; Novellino, F.; Salsone, M.; Barbagallo, G.; Quattrone, A.
Abstract: Parkinson disease (PD) can be considered as a brain multisystemic disease arising from dysfunction in several neural networks. The principal aim of this study was to assess whether large‐scale structural topological network changes are detectable in PD patients who have not been exposed yet to dopaminergic therapy (de novo patients). Twenty‐one drug‐naïve PD patients and thirty healthy controls underwent a 3T structural MRI. Next, Diffusion Tensor Imaging (DTI) and graph theoretic analyses to compute individual structural white‐matter (WM) networks were combined. Centrality (degree, eigenvector centrality), segregation (clustering coefficient), and integration measures (efficiency, path length) were assessed in subject‐specific structural networks. Moreover, Network‐based statistic (NBS) was used to identify whether and which subnetworks were significantly different between PD and control participants. De novo PD patients showed decreased clustering coefficient and strength in specific brain regions such as putamen, pallidum, amygdala, and olfactory cortex compared with healthy controls. Moreover, NBS analyses demonstrated that two specific subnetworks of reduced connectivity characterized the WM structural organization of PD patients. In particular, several key pathways in the limbic system, basal ganglia, and sensorimotor circuits showed reduced patterns of communications when comparing PD patients to controls. This study shows that PD is characterized by a disruption in the structural connectivity of several motor and non‐motor regions. These findings provide support to the presence of disconnectivity mechanisms in motor (basal ganglia) as well as in non‐motor (e.g., limbic, olfactory) circuits at an early disease stage of PD. Hum Brain Mapp 37:4500–4510, 2016 . ©2016 Wiley Periodicals, Inc.